2017
DOI: 10.3390/ijms18081654
|View full text |Cite
|
Sign up to set email alerts
|

A Different Microbiome Gene Repertoire in the Airways of Cystic Fibrosis Patients with Severe Lung Disease

Abstract: In recent years, next-generation sequencing (NGS) was employed to decipher the structure and composition of the microbiota of the airways in cystic fibrosis (CF) patients. However, little is still known about the overall gene functions harbored by the resident microbial populations and which specific genes are associated with various stages of CF lung disease. In the present study, we aimed to identify the microbial gene repertoire of CF microbiota in twelve patients with severe and normal/mild lung disease by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 80 publications
(88 reference statements)
1
39
0
Order By: Relevance
“…More importantly, although most of the species identified in PM 10 samples displayed significant differences in relative abundance between a low AQI level (I or II) and a high AQI level (IV or V), none in PM 2.5 exhibited such patterns (Wilcoxon rank-sum test, adjusted P < 0.1, Additional file 1: Tables 12). The microbes included those associated with human infections, such as Pseudomonas aeruginosa [26,27], with a positive correlation with pollutant concentration for both PM 2.5 and PM 10 samples (adjusted P < 0.05), and Stenotrophomonas maltophilia [28], with a positive correlation with the pollutant concentration in PM 10 samples. In addition, 72 microbes manifested prominent peaks in January (Additional file 2: Figure S12) when the air pollution was most severe.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, although most of the species identified in PM 10 samples displayed significant differences in relative abundance between a low AQI level (I or II) and a high AQI level (IV or V), none in PM 2.5 exhibited such patterns (Wilcoxon rank-sum test, adjusted P < 0.1, Additional file 1: Tables 12). The microbes included those associated with human infections, such as Pseudomonas aeruginosa [26,27], with a positive correlation with pollutant concentration for both PM 2.5 and PM 10 samples (adjusted P < 0.05), and Stenotrophomonas maltophilia [28], with a positive correlation with the pollutant concentration in PM 10 samples. In addition, 72 microbes manifested prominent peaks in January (Additional file 2: Figure S12) when the air pollution was most severe.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported on the dynamics of antibiotic resistance expression in the gut and in the environmental microbiome, and have shown the diversity in ARG expression and niche specificity [10,22]. Other studies have shown the presence of ARGs in the lungs of cystic fibrosis patients [23], and in the stool of individuals who had never been exposed to antibiotics [24]. In our study, we identified bacteria-expressed genes that confer resistance to classes of antibiotics that the infected individuals were not taking, according to their antibiotic use history in the 12 months preceding influenza diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant bacterial species in CF, such as P. aeruginosa [69] and Staphylococcus aureus [70,71], possess large, flexible gene pools, including genes encoding antibiotic resistance, pathogenicity, environmental response, and metabolic flexibility, which may explain the adaptive nature of chronic infections [72]. Although the metagenome contributes greatly to interactions with the host [25,73], very few studies on CF metagenomes have been performed, involving a limited number of both patients [29,63,74,75] and specific metabolic functions [76]. By analyzing the abundance of specific genes, such studies found a homogeneous distribution of predicted bacterial community activities (e.g., specific metabolic pathways) across patients with similar pulmonary function, as indicated by forced expiratory volume in 1 second (FEV 1 ) [73], suggesting a relationship between microbiome function and clinical status.…”
Section: Many Singers But Which Song(s)?mentioning
confidence: 99%
“…Although the metagenome contributes greatly to interactions with the host [25,73], very few studies on CF metagenomes have been performed, involving a limited number of both patients [29,63,74,75] and specific metabolic functions [76]. By analyzing the abundance of specific genes, such studies found a homogeneous distribution of predicted bacterial community activities (e.g., specific metabolic pathways) across patients with similar pulmonary function, as indicated by forced expiratory volume in 1 second (FEV 1 ) [73], suggesting a relationship between microbiome function and clinical status. This finding is in line with other metagenomic studies in humans and other systems, suggesting that changing the taxonomic composition does not drastically alter the functional capacity of the microbiome (see [77] for a comprehensive list of studies).…”
Section: Many Singers But Which Song(s)?mentioning
confidence: 99%